Comparative evaluation of an AI-powered life coach against traditional coaching methods - David Brown; Marlene Orozco; Noah Lloyd (International Journal of Evidence Based Coaching and Mentoring)
This study assesses the efficacy of “1440”, an AI-powered life coaching tool, in comparison to traditional human coaching. Utilizing a controlled experimental design, participants were divided into three distinct groups and engaged in a standardized coaching scenario. The study evaluates the performance of 1440 across multiple key metrics, including goal achievement, satisfaction, and perceived support. The empirical findings indicate that 1440 significantly outperforms traditional human coaching in several critical dimensions, suggesting its potential as a scalable and accessible alternative for personal development and professional growth.